A dry direct-injection recycled asphalt mixture and its preparation method

Through the combination of dry direct injection process and composite modifier, the problem of insufficient self-repair performance of asphalt mixture is solved, the mechanical properties and rut resistance of asphalt mixture are improved, and the recycling and utilization of waste asphalt is promoted.

CN118955009BActive Publication Date: 2025-04-08ZHONGYIFENG (SUZHOU) MATERIALS TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411007050.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-25
Publication Date
2025-04-08
Estimated Expiration
2044-07-25

AI Technical Summary

Technical Problem

The prior art fails to impart self-repairing properties to asphalt mixtures, resulting in poor maintenance of mechanical properties and rut resistance, and fails to effectively utilize waste and aged asphalt.

Method used

The regenerated asphalt mixture is prepared by dry direct pouring process, and by combining components such as luteolin-based epoxy resin, block copolymer rubber and nitrile rubber with regenerated asphalt and composite aggregates, a composite modifier with self-healing properties is formed.

Benefits of technology

The mechanical properties and rut resistance of the asphalt mixture are improved, the efficient utilization of recycled asphalt is achieved, and the construction process is simplified through the dry direct injection process, which improves the dosage and distribution accuracy of the modifier.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004963274430000021
    Figure BDA0004963274430000021
  • Figure BDA0004963274430000031
    Figure BDA0004963274430000031
  • Figure BDA0004963274430000131
    Figure BDA0004963274430000131
Patent Text Reader

Abstract

The invention discloses a dry direct-throw recycled asphalt mixture and a preparation method thereof, and belongs to the technical field of asphalt mixtures. The invention is used to solve the technical problem that traditional asphalt mixtures cannot regenerate waste aged asphalt and the asphalt mixtures have poor mechanical properties and rutting resistance. The invention comprises recycled asphalt, a composite modifier and a composite aggregate. The recycled asphalt is obtained by mixing waste edible oil and aged asphalt, a block copolymer rubber is prepared by natural rubber NR and zinc dimethacrylate, and the block copolymer rubber, nitrile rubber and luteolin-based epoxy resin are compounded to obtain a self-repairing and highly elastic composite modifier. The inorganic powder is modified by chloroalkylsilane to improve the mechanical properties of the composite aggregate. The asphalt mixture prepared in the invention has the advantages of recycled aged asphalt, strong mechanical properties and repeated rutting resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of asphalt mixtures, and in particular relates to a dry direct-throw recycled asphalt mixture and a preparation method thereof. Background Art

[0002] Asphalt pavement is the main pavement structure form of highways. A large amount of waste asphalt mixture is generated during the maintenance or resurfacing process of asphalt pavement. If it is not handled promptly and properly, it will easily lead to waste of resources and serious pollution problems. The key to recycling old asphalt materials is to achieve the recycling of aged asphalt. In addition, in order to extend the service life of asphalt pavement and make it more suitable for use in environments with frequent heavy traffic, it is necessary to improve the rutting resistance and mechanical properties of the pavement by modifying the asphalt mixture.

[0003] Patent application CN116375394A discloses a direct-cast modified ultra-thin wear layer asphalt mixture and its construction process. The above-mentioned asphalt mixture includes a dry composite modifier, heavy-duty petroleum asphalt and aggregate. The interfacial cross-linking agent forms a double-bond cross-linked stable structure with rubber powder, thermoplastic rubber SBS and petroleum asphalt through double bonds, thereby reducing the construction temperature of the asphalt mixture; however, the above-mentioned prior art fails to give the asphalt mixture self-repairing properties, so that it maintains its own mechanical properties and poor rutting resistance. In addition, how to recycle waste and aged asphalt is still a technical problem that needs to be solved urgently. Summary of the invention

[0004] The purpose of the present invention is to provide a dry direct-throw recycled asphalt mixture and a preparation method thereof, so as to solve the technical problem in the prior art that the elasticity and mechanical properties of the asphalt mixture are improved only by forming a cross-linked structure through a modifier, but the asphalt mixture fails to maintain mechanical properties and rutting resistance.

[0005] The purpose of the present invention can be achieved by the following technical scheme: A dry direct-throw recycled asphalt mixture, comprising the following components in parts by weight: 10-20 parts of recycled asphalt, 10-20 parts of composite modifier and 80 parts of composite aggregate;

[0006] The preparation method of the composite modifier comprises the following steps:

[0007] S1, luteolin and ethanol are mixed to obtain a luteolin solution; tetrabutylammonium bromide and epichlorohydrin are added to the luteolin solution to obtain a mixed solid-liquid; the mixed solid-liquid is reacted at 70-75° C. for 2-3 hours, and a NaOH solution is added dropwise during the reaction to maintain the pH value of the mixed solid-liquid at 8-10; then filtered to obtain a solid; the solid is washed with deionized water and vacuum dried to obtain a luteolin-based epoxy resin;

[0008] Luteolin, as an organic compound containing polyphenolic hydroxyl groups, can undergo nucleophilic substitution reaction with chloride ions in epichlorohydrin to prepare luteolin-based epoxy resin.

[0009] The reaction formula of luteolin and epichlorohydrin is as follows:

[0010]

[0011] S2, adding natural rubber NR into the torque rheometer and mixing for 2-5 minutes, then adding zinc dimethacrylate into the torque rheometer, and then adding initiator, mixing at 80-85° C. for 5-10 minutes to obtain a block copolymer rubber;

[0012] Natural rubber NR is used as the rubber material. Under the action of an initiator, zinc dimethacrylate is used as a grafting monomer and the materials are mixed in a mixer to achieve graft copolymerization.

[0013] The reaction formula of natural rubber NR and zinc dimethacrylate is as follows:

[0014]

[0015] S3, block copolymer rubber, nitrile rubber and luteolin-based epoxy resin are mixed at 90° C. for 5-10 minutes to obtain a composite rubber material; the composite rubber material is added to a tablet press for vulcanization to obtain a composite modifier.

[0016] The rubber material, grafting monomer and initiator are mixed together in a mixer to achieve graft copolymerization to prepare a block copolymer rubber; specifically, zinc dimethacrylate is used as an ionic compound. Under the initiation of peroxide free radicals, zinc dimethacrylate can be grafted onto the molecular chain of the rubber. 2+ As an auxiliary agent for rubber grafting, salt bonds are also added to the rubber network. All these restrictions promote the entire cross-linking network to form a new ion cross-linking network. The reversible ion cross-linking network enables the prepared composite modifier to have self-healing properties. In the torque rheometer, the phenolic hydroxyl group and epoxy group contained in the luteolin-based epoxy resin prepared by the present invention can react with the carboxyl group in the nitrile rubber to prepare a composite cross-linking agent.

[0017] Furthermore, the dosage ratio of luteolin, ethanol, tetrabutylammonium bromide and epichlorohydrin is 25-30 g:200 mL:1-3 g:10-20 g; the vacuum drying temperature is 50-60° C., and the vacuum drying time is 30 min.

[0018] Furthermore, the initiator is dicumyl peroxide, and the amount ratio of natural rubber NR, zinc dimethacrylate and initiator is 300g:60-100g:3-5g; in step S3, the amount ratio of nitrile rubber and luteolin-based epoxy resin is 200g:200-240g; the vulcanization temperature is 140°C, the vulcanization time is 5-10min, and the vulcanization pressure is 10MPa.

[0019] Furthermore, the method for preparing the regenerated asphalt comprises the following steps:

[0020] The base asphalt is added to an aging tray, and the aging tray is then aged at 165-175°C for 5 hours to obtain aged asphalt. The aged asphalt is mixed with waste cooking oil to obtain a mixture, and the mixture is sheared at a high speed at 120-130°C to obtain regenerated asphalt.

[0021] No. 70 Grade A asphalt is used as base asphalt, and the base asphalt is subjected to aging reaction under simulated conditions to obtain aged asphalt, and the aged asphalt is mixed with waste cooking oil to prepare recycled asphalt.

[0022] Furthermore, the usage ratio of aged asphalt and waste cooking oil is 100g:5-10g, the high-speed shearing speed is 2000-3000r / min, and the high-speed shearing time is 20-40min.

[0023] Furthermore, the method for preparing the composite aggregate comprises the following steps:

[0024] A1, trichlorosilane, chloropropylene and a platinum catalyst are mixed to obtain a mixture; the mixture is reacted at 80-85° C. for 10-15 hours to obtain a product; the product is distilled under normal pressure, and a fraction at 179-180° C. is cut to obtain a chloroalkylsilane;

[0025] Under the action of homogeneous platinum catalyst, trichlorosilane and allyl chloride undergo hydrogen silane addition to obtain the coupling agent chloroalkylsilane.

[0026] A2, diatomite and expanded perlite are mixed evenly to obtain a heat-insulating refractory material;

[0027] A3, graphene oxide and thermal insulation refractory materials are mixed uniformly to obtain a mixture; the mixture is ground and passed through a 2.36 mm sieve to obtain a primary batching; the mixture is ground and passed through a 4.75 mm sieve to obtain a secondary batching; the mixture is ground and passed through a 16 mm sieve to obtain a tertiary batching; the primary batching, the secondary batching and the tertiary batching are mixed uniformly to obtain a composite aggregate;

[0028] A4. Evenly mix the chloroalkylsilane and the composite inorganic substance to obtain a composite aggregate.

[0029] Using chloroalkylsilane as coupling agent, the mixture is modified by chloroalkylsilane to obtain organic modified composite aggregate.

[0030] The composite aggregate components prepared in the present invention include diatomaceous earth, expanded perlite and graphene oxide. The prepared composite grade materials are respectively passed through a sieve hole of 2.36 mm, a sieve hole of 4.75 mm and a sieve hole of 16 mm, and the sizes of each grade are 9.5-13.2 mm, 2.36-4.75 mm and 0.075-2.36 mm, respectively. The powders of the above-mentioned diameters are evenly mixed to obtain the composite aggregate.

[0031] Furthermore, the dosage ratio of trichlorosilane, propylene chloride and platinum catalyst is 13g:7-10g:1-3g; in step A2, the dosage ratio of diatomaceous earth and expanded perlite is 30g:30g; in step A3, the dosage ratio of graphene oxide and thermal insulation refractory material is 10g:30-60g; the dosage ratio of primary ingredients, secondary ingredients and tertiary ingredients is 10g:10g:10g.

[0032] Furthermore, a method for preparing a direct-invested recycled asphalt mixture comprises the following steps:

[0033] B1. Heat the composite aggregate to 180-190° C. to obtain heated aggregate;

[0034] B2. Add the heated aggregate into the mixing tank, and then pre-mix the heated aggregate and the composite modifier. The pre-mixing time is 5 seconds;

[0035] B3. Then add recycled asphalt into the mixing tank and mix evenly. Set the dry mixing time to 10s and the wet mixing time to 45s to obtain a dry direct-throw recycled asphalt mixture.

[0036] The present invention has the following beneficial effects:

[0037] 1. The regenerated asphalt mixture prepared by the present invention includes regenerated asphalt, a composite modifier and a composite aggregate; the present invention adopts a dry direct investment process to prepare the regenerated asphalt mixture, that is, the composite modifier is directly added into the mixing equipment in a dry form, dry-mixed with the composite aggregate, and then the regenerated asphalt is added for wet mixing, thereby obtaining the regenerated asphalt mixture; the dry direct investment process has a simpler construction process, and by directly adding the composite modifier, the amount and distribution of the modifier can be accurately controlled, thereby improving the modification effect. The present invention mixes aged asphalt and waste cooking oil to prepare regenerated asphalt; waste cooking oil and aged asphalt have similar rheological properties and high compatibility with aged asphalt, and the addition of waste cooking oil makes the aged asphalt have better high and low temperature resistance; in addition, the composition of waste cooking oil is extremely complex, containing a variety of fatty acids and unsaturated fatty acids, including palmitic acid, oleic acid and linoleic acid, etc., especially containing functional groups such as carboxyl, carbon-carbon double bonds and aldehyde groups, so that the regenerated asphalt reacts with the functional groups of the composite modifier and the organic components of the composite aggregate, thereby improving the integrity and mechanical properties of the prepared asphalt mixture.

[0038] 2. Under the action of initiator, natural rubber NR and zinc dimethacrylate are grafted and copolymerized to prepare block copolymer rubber; in addition, Zn 2+ It is also possible to add salt bonds to natural rubber NR to form new ionic crosslinks, thereby forming block copolymer rubber; ionic crosslinks have the characteristics of breaking and rebuilding, so that the rubber segments are rearranged, thereby giving the rubber potential self-repairing ability; the block copolymer rubber with an ionic crosslinking network has self-healing properties, thereby maintaining its own mechanical properties; the nitrile rubber, luteolin-based epoxy resin and block copolymer rubber are mixed to prepare a composite modifier with high elasticity. The composite inorganic material used in the composite aggregate of the present invention includes diatomaceous earth, expanded perlite and graphene oxide; graphene oxide, as a derivative of graphene, is derived from a mixture of carboxyl, hydroxyl and epoxy functional groups to form SP 2 The hybridized carbon atom monolayer can react with the multifunctional groups in the recycled asphalt and composite modifier to improve the integrity of the composite aggregate and other components; the use of graphene oxide in the composite aggregate can effectively improve the compressive strength and flexural strength of asphalt concrete; the pores of diatomaceous earth are very small, and its thermal conductivity is very small, which has a good shielding effect on heat; the expanded perlite not only has excellent heat resistance, but also is resistant to acid and alkali corrosion, that is, the composite aggregate and recycled asphalt mixture prepared by the present invention have thermal insulation properties. The chlorosilicon coupling agent can react with the carboxyl and aldehyde functional groups in the waste cooking oil of the recycled asphalt, and the synthesized chlorosilicon coupling agent can react with the double bonds and carboxyl groups in the composite modifier, thereby improving the integrity and elastic deformation resistance of the prepared asphalt mixture, which is manifested as the enhancement of the mechanical properties of the asphalt mixture. DETAILED DESCRIPTION

[0039] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Example 1

[0041] This embodiment provides a method for preparing regenerated asphalt for dry direct-throw regenerated asphalt mixture, comprising the following steps:

[0042] 1. Add 100 g of 70#A grade asphalt into a stainless steel aging tray, and then place the stainless steel aging tray into a film oven, set the temperature to 165°C, and age for 5 hours to obtain aged asphalt.

[0043] 2. Mix 100 g of aged asphalt and 5 g of waste cooking oil to obtain a mixture; add the mixture into a high-speed shearing machine, and shear at a shear speed of 2000 r / min at 120°C for 20 minutes to obtain regenerated asphalt.

[0044] Example 2

[0045] This embodiment provides a method for preparing regenerated asphalt for dry direct-throw regenerated asphalt mixture, comprising the following steps:

[0046] 1. Pour 100g of 70#A grade asphalt into a stainless steel aging tray, and then put the stainless steel aging tray into a film oven, set the temperature to 170°C, and the aging time to 5h to obtain aged asphalt.

[0047] 2. Mix 100 g of aged asphalt and 8 g of waste cooking oil to obtain a mixture; add the mixture into a high-speed shearing machine, and shear at a shear speed of 2500 r / min at 125°C for 30 minutes to obtain regenerated asphalt.

[0048] Example 3

[0049] This embodiment provides a method for preparing regenerated asphalt for dry direct-throw regenerated asphalt mixture, comprising the following steps:

[0050] 1. Pour 100g of 70#A grade asphalt into a stainless steel aging tray, and then put the stainless steel aging tray into a film oven, set the temperature to 175°C, and the aging time to 5h to obtain aged asphalt.

[0051] 2. Mix 100 g of aged asphalt and 10 g of waste cooking oil to obtain a mixture; add the mixture into a high-speed shearing machine, and shear at a shear speed of 3000 r / min at 130°C for 40 minutes to obtain regenerated asphalt.

[0052] Example 4

[0053] This embodiment provides a method for preparing a composite modifier for dry direct-addition recycled asphalt mixture, comprising the following steps:

[0054] 1. Add 25 g of luteolin and 200 mL of ethanol into a 500 mL beaker, stir at room temperature at 100 r / min for 30 min to obtain a luteolin solution; then add 1 g of tetrabutylammonium bromide and 10 g of epichlorohydrin into the beaker to obtain a mixed solid-liquid; then transfer the beaker to a water bath, set the temperature of the water bath to 70 ° C, and react for 2 h with mechanical stirring at 100 r / min. During the reaction, add 0.1 mol / L NaOH solution dropwise to keep the pH value of the mixed solid-liquid at 8; filter the mixed solid-liquid to obtain a solid; wash the solid three times with deionized water, and vacuum dry it at 50 ° C for 30 min to obtain a luteolin-based epoxy resin.

[0055] 2. In a torque rheometer, add 300g of natural rubber NR and mix for 2min, then slowly add 60g of zinc dimethacrylate into the torque rheometer in three batches, add 3g of initiator diisopropylbenzene peroxide, mix at 80°C for 5min to obtain a block copolymer rubber; after the block copolymer rubber is naturally cooled to room temperature, add 200g of nitrile rubber and 200g of luteolin-based epoxy resin into the multi-torque rheometer, mix at 90°C for 5min to obtain a composite rubber; add the composite rubber to a tablet press for vulcanization, wherein the vulcanization temperature is 140°C, the vulcanization time is 5min, and the vulcanization pressure is 10MPa to obtain a composite modifier.

[0056] Example 5

[0057] This embodiment provides a method for preparing a composite modifier for dry direct-addition recycled asphalt mixture, comprising the following steps:

[0058] 1. Add 26 g of luteolin and 200 mL of ethanol into a 500 mL beaker, stir at room temperature at 150 r / min for 30 min to obtain a luteolin solution; then add 2 g of tetrabutylammonium bromide and 15 g of epichlorohydrin into the beaker to obtain a mixed solid-liquid; then transfer the beaker to a water bath, set the temperature of the water bath to 72 ° C, and react for 2.3 h with mechanical stirring at 160 r / min. During the reaction, add 0.1 mol / L NaOH solution dropwise to keep the pH value of the mixed solid-liquid at 9; filter the mixed solid-liquid to obtain a solid; wash the solid three times with deionized water, and vacuum dry it at 55 ° C for 30 min to obtain a luteolin-based epoxy resin.

[0059] 2. In a torque rheometer, add 300g of natural rubber NR and mix for 3min, then slowly add 80g of zinc dimethacrylate into the torque rheometer in three batches, add 4g of initiator diisopropylbenzene peroxide, mix at 82°C for 6min, and obtain a block copolymer rubber; after the block copolymer rubber is naturally cooled to room temperature, add 200g of nitrile rubber and 220g of luteolin-based epoxy resin into the multi-torque rheometer, mix at 90°C for 8min, and obtain a composite rubber; add the composite rubber to a tablet press for vulcanization, wherein the vulcanization temperature is 140°C, the vulcanization time is 8min, and the vulcanization pressure is 10MPa, to obtain a composite modifier.

[0060] Example 6

[0061] This embodiment provides a method for preparing a composite modifier for dry direct-addition recycled asphalt mixture, comprising the following steps:

[0062] 1. Add 30 g of luteolin and 200 mL of ethanol into a 500 mL beaker, stir at 200 r / min for 30 min at room temperature to obtain a luteolin solution; then add 3 g of tetrabutylammonium bromide and 20 g of epichlorohydrin into the beaker to obtain a mixed solid-liquid; then transfer the beaker to a water bath, set the temperature of the water bath to 75 ° C, and react for 3 h with mechanical stirring at 200 r / min. During the reaction, add 0.1 mol / L NaOH solution dropwise to keep the pH value of the mixed solid-liquid at 10; filter the mixed solid-liquid to obtain a solid; wash the solid three times with deionized water, and vacuum dry it at 60 ° C for 30 min to obtain a luteolin-based epoxy resin.

[0063] 2. In a torque rheometer, add 300g of natural rubber NR and mix for 5min, then slowly add 100g of zinc dimethacrylate into the torque rheometer in three batches, add 5g of initiator diisopropylbenzene peroxide, mix at 85°C for 10min to obtain a block copolymer rubber; after the block copolymer rubber is naturally cooled to room temperature, add 200g of nitrile rubber and 240g of luteolin-based epoxy resin into the multi-torque rheometer, mix at 90°C for 10min to obtain a composite rubber; add the composite rubber to a tablet press for vulcanization, wherein the vulcanization temperature is 140°C, the vulcanization time is 10min, and the vulcanization pressure is 10MPa to obtain a composite modifier.

[0064] Example 7

[0065] This embodiment provides a method for preparing composite aggregate for dry direct-throw recycled asphalt mixture, comprising the following steps:

[0066] 1. Connect a 1000mL three-necked flask with a reflux condenser, a thermometer and a dropping funnel. Add 13g of trichlorosilane, 7g of chloropropylene and 1g of platinum catalyst into the three-necked flask and mix and stir to obtain a mixture. Connect the outlet of the three-necked flask with a CaCl 2 The three-necked flask was dried and then heated to 80°C for reflux reaction for 10 hours to obtain a product; the product was added to a distillation apparatus for atmospheric distillation, and the fraction at 179°C was cut to obtain chloroalkylsilane.

[0067] 2. 30g of diatomaceous earth and 30g of expanded perlite are mixed evenly to obtain a thermal insulation refractory material; 10g of graphene oxide and 30g of thermal insulation refractory material are mixed evenly to obtain a mixture; the mixture is ground and passed through a 2.36mm sieve to obtain a primary ingredient; the mixture is ground and passed through a 4.75mm sieve to obtain a secondary ingredient; the mixture is ground and passed through a 16mm sieve to obtain a tertiary ingredient; 10g of the primary ingredient, 10g of the secondary ingredient and 10g of the tertiary ingredient are mixed evenly to obtain a composite inorganic substance.

[0068] 3. Evenly mix 10 g of chloroalkylsilane and 50 g of composite inorganic material to obtain composite aggregate.

[0069] Example 8

[0070] This embodiment provides a method for preparing composite aggregate for dry direct-throw recycled asphalt mixture, comprising the following steps:

[0071] 1. Connect a 1000mL three-necked flask with a reflux condenser, a thermometer and a dropping funnel. Add 13g of trichlorosilane, 8g of chloropropylene and 2g of platinum catalyst into the three-necked flask and mix and stir to obtain a mixture. Connect the outlet of the three-necked flask with a CaCl 2The three-necked flask was dried and then heated to 82°C for 12 hours of reflux reaction to obtain a product; the product was added to a distillation apparatus for atmospheric distillation, and a fraction at 179°C was cut to obtain chloroalkylsilane.

[0072] 2. 30g of diatomaceous earth and 30g of expanded perlite are mixed evenly to obtain a thermal insulation refractory material; 10g of graphene oxide and 40g of thermal insulation refractory material are mixed evenly to obtain a mixture; the mixture is ground and passed through a 2.36mm sieve to obtain a primary ingredient; the mixture is ground and passed through a 4.75mm sieve to obtain a secondary ingredient; the mixture is ground and passed through a 16mm sieve to obtain a tertiary ingredient; 10g of the primary ingredient, 10g of the secondary ingredient and 10g of the tertiary ingredient are mixed evenly to obtain a composite inorganic substance.

[0073] 3. Mix 20 g of chloroalkylsilane and 50 g of composite inorganic material evenly to obtain composite aggregate.

[0074] Example 9

[0075] This embodiment provides a method for preparing composite aggregate for dry direct-throw recycled asphalt mixture, comprising the following steps:

[0076] 1. Connect a 1000mL three-necked flask with a reflux condenser, a thermometer and a dropping funnel. Add 13g of trichlorosilane, 10g of chloropropylene and 3g of platinum catalyst into the three-necked flask and mix and stir to obtain a mixture. Connect the outlet of the three-necked flask with a CaCl 2 The three-necked flask was dried and then heated to 85°C for 15 hours of reflux reaction to obtain a product; the product was added to a distillation apparatus for atmospheric distillation, and the fraction at 180°C was cut to obtain chloroalkylsilane.

[0077] 2. 30g of diatomaceous earth and 30g of expanded perlite are mixed evenly to obtain a thermal insulation refractory material; 10g of graphene oxide and 60g of thermal insulation refractory material are mixed evenly to obtain a mixture; the mixture is ground and passed through a 2.36mm sieve to obtain a primary ingredient; the mixture is ground and passed through a 4.75mm sieve to obtain a secondary ingredient; the mixture is ground and passed through a 16mm sieve to obtain a tertiary ingredient; 10g of the primary ingredient, 10g of the secondary ingredient and 10g of the tertiary ingredient are mixed evenly to obtain a composite inorganic substance.

[0078] 3. Mix 30 g of chloroalkylsilane and 50 g of composite inorganic material evenly to obtain composite aggregate.

[0079] Example 10

[0080] This embodiment provides a method for preparing a dry direct-throw recycled asphalt mixture, comprising the following steps:

[0081] According to parts by weight, 80 parts of the composite aggregate prepared in Example 7 are heated to 180°C to obtain heated aggregate; the heated aggregate is added to a mixing tank, and then 10 parts of the composite modifier prepared in Example 4 are added to the mixing tank for pre-mixing for 5 seconds, and then 10 parts of the regenerated asphalt prepared in Example 1 are added and mixed evenly, and the dry mixing time is set to 10 seconds and the wet mixing time is set to 45 seconds, and then the material is discharged to prepare a dry direct-throw regenerated asphalt mixture.

[0082] Embodiment 11

[0083] This embodiment provides a method for preparing a dry direct-throw recycled asphalt mixture, comprising the following steps:

[0084] According to parts by weight, 85 parts of the composite aggregate prepared in Example 8 are heated to 183°C to obtain heated aggregate; the heated aggregate is added to a mixing tank, and then 15 parts of the composite modifier prepared in Example 5 are added to the mixing tank and pre-mixed for 6 seconds, and then 15 parts of the regenerated asphalt prepared in Example 2 are added and mixed evenly, and the dry mixing time is set to 10 seconds and the wet mixing time is set to 45 seconds, and then the material is discharged to prepare a dry direct-throw regenerated asphalt mixture.

[0085] Example 12

[0086] This embodiment provides a method for preparing a dry direct-throw recycled asphalt mixture, comprising the following steps:

[0087] According to parts by weight, 90 parts of the composite aggregate prepared in Example 9 are heated to 190°C to obtain heated aggregate; the heated aggregate is added to a mixing tank, and then 20 parts of the composite modifier prepared in Example 6 are added to the mixing tank and pre-mixed for 10 seconds, and then 20 parts of the regenerated asphalt prepared in Example 3 are added and mixed evenly, and the dry mixing time is set to 10 seconds and the wet mixing time is set to 45 seconds, and then the material is discharged to prepare a dry direct-throw regenerated asphalt mixture.

[0088] Comparative Example 1

[0089] The difference between this comparative example and Example 3 is that the aged asphalt is not mixed with waste cooking oil, and the regenerated asphalt is directly obtained.

[0090] Comparative Example 2

[0091] The difference between this comparative example and Example 12 is that no nitrile rubber is added to the composite modifier.

[0092] Comparative Example 3

[0093] The difference between this comparative example and Example 12 is that when preparing the composite aggregate, no chloroalkylsilane-modified composite inorganic material is used.

[0094] Performance Test:

[0095] 1. According to the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering", a viscosity test was conducted on the regenerated asphalt prepared in Examples 1-3 and Comparative Example 1 using a Brookfield viscometer, and the test temperature was 60°C.

[0096] The test results are shown in Table 1:

[0097] Table 1 - Performance test data table

[0098]

[0099] Data Analysis:

[0100] The regenerated asphalts prepared in Examples 1-3 of the present invention all have excellent rheological properties. Since waste cooking oil and regenerated asphalt have similar rheological properties, adding a certain amount of waste cooking oil to the regenerated asphalt can increase the elastic component in the regenerated asphalt and improve its own viscosity, thereby improving the rutting resistance of the regenerated asphalt mixture; however, in Comparative Example 1, since no waste cooking oil was added, the elastic component in the aged asphalt continued to decrease, the fluidity of the regenerated asphalt was enhanced, and the viscosity value was reduced, thereby reducing its own rutting resistance.

[0101] 2. A rutting test was performed on the regenerated asphalt mixture prepared in Examples 10-12 to determine its 45-min deformation and 60-min deformation.

[0102] 3. A low-temperature small beam bending test was used to detect the flexural tensile strength and stiffness modulus values ​​of the regenerated asphalt mixtures prepared in Examples 10-12.

[0103] Table 2 - Performance test data table

[0104]

[0105] Data Analysis:

[0106] The regenerated asphalt mixtures prepared in Examples 10-12 of the present invention have excellent rutting resistance, which is manifested by strong resistance to elastic deformation, and have smaller deformation values ​​at 45min and 60min; however, in Comparative Example 2, no nitrile rubber was added when preparing the asphalt mixture, and the luteolin-based epoxy resin and the block copolymer rubber lacked an intermediate elastomer for cross-linking, which reduced the resistance of the prepared regenerated asphalt mixture to elastic deformation, which was manifested by an increase in the deformation values ​​at 45min and 60min.

[0107] The regenerated asphalt mixtures prepared in Examples 10-12 of the present invention all have excellent mechanical properties, as shown by high values ​​of flexural tensile strength and stiffness modulus. In Comparative Example 3, the composite aggregate was prepared without modification with chloroalkylsilane, which reduced the integrity between the components of the composite aggregate and between the composite aggregate and other components of the asphalt mixture, thereby reducing the mechanical properties of the regenerated asphalt mixtures prepared in Examples 10-12, as shown by reduced values ​​of flexural tensile strength and stiffness modulus.

[0108] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0109] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0110] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A dry direct-throw recycled asphalt mixture, characterized in that: The invention comprises the following components in parts by weight: 10-20 parts of recycled asphalt, 10-20 parts of composite modifier and 80 parts of composite aggregate; The preparation method of the composite modifier comprises the following steps: S1, luteolin and ethanol are mixed to obtain a luteolin solution; tetrabutylammonium bromide and epichlorohydrin are added to the luteolin solution to obtain a mixed solid-liquid; the mixed solid-liquid is reacted at 70-75° C. for 2-3 hours, and a NaOH solution is added dropwise during the reaction to maintain the pH value of the mixed solid-liquid at 8-10; then filtered to obtain a solid; the solid is washed with deionized water and vacuum dried to obtain a luteolin-based epoxy resin; S2, adding natural rubber NR into the torque rheometer and mixing for 2-5 minutes, then adding zinc dimethacrylate into the torque rheometer, and then adding initiator, mixing at 80-85° C. for 5-10 minutes to obtain a block copolymer rubber; S3, block copolymer rubber, nitrile rubber and luteolin-based epoxy resin are mixed at 90° C. for 5-10 minutes to obtain a composite rubber; the composite rubber is added to a tablet press for vulcanization to obtain a composite modifier; The method for preparing the regenerated asphalt comprises the following steps: The base asphalt is added to an aging tray, and the aging tray is aged at 165-175° C. for 5 hours to obtain aged asphalt; the aged asphalt is mixed with waste cooking oil to obtain a mixture; the mixture is sheared at a high speed at 120-130° C. to obtain aged asphalt; The method for preparing the composite aggregate comprises the following steps: A1, trichlorosilane, chloropropylene and a platinum catalyst are mixed to obtain a mixture; the mixture is reacted at 80-85° C. for 10-15 hours to obtain a product; the product is distilled under normal pressure, and a fraction at 179-180° C. is cut to obtain a chloroalkylsilane; A2, diatomite and expanded perlite are mixed evenly to obtain a heat-insulating refractory material; A3, graphene oxide and thermal insulation refractory material are mixed uniformly to obtain a mixture; the mixture is ground and passed through a 2.36 mm sieve to obtain a primary batching; the mixture is ground and passed through a 4.75 mm sieve to obtain a secondary batching; the mixture is ground and passed through a 16 mm sieve to obtain a tertiary batching; the primary batching, the secondary batching and the tertiary batching are mixed uniformly to obtain a composite inorganic substance; A4. Evenly mix the chloroalkylsilane and the composite inorganic substance to obtain a composite aggregate.

2. The dry direct-throw recycled asphalt mixture according to claim 1, characterized in that: In step S1, the usage ratio of luteolin, ethanol, tetrabutylammonium bromide and epichlorohydrin is 25-30 g:200 mL:1-3 g:10-20 g; the vacuum drying temperature is 50-60° C., and the vacuum drying time is 30 min.

3. The dry direct-throw recycled asphalt mixture according to claim 1, characterized in that: In step S2, the initiator is dicumyl peroxide, and the amount ratio of natural rubber NR, zinc dimethacrylate and initiator is 300g:60-100g:3-5g; in step S3, the amount ratio of nitrile rubber and luteolin-based epoxy resin is 200g:200-240g; the vulcanization temperature is 140°C, the vulcanization time is 5-10min, and the vulcanization pressure is 10MPa.

4. The dry direct-throw recycled asphalt mixture according to claim 1, characterized in that: The dosage ratio of aged asphalt and waste cooking oil is 100g:5-10g, the high-speed shearing speed is 2000-3000r / min, and the high-speed shearing time is 20-40min.

5. The dry direct-throw recycled asphalt mixture according to claim 1, characterized in that: In step A1, the dosage ratio of trichlorosilane, chloropropylene and platinum catalyst is 13g:7-10g:1-3g; in step A2, the dosage ratio of diatomaceous earth and expanded perlite is 30g:30g; in step A3, the dosage ratio of graphene oxide and thermal insulation refractory material is 10g:30-60g; the dosage ratio of primary ingredients, secondary ingredients and tertiary ingredients is 10g:10g:10g; in step A4, the dosage ratio of chloroalkylsilane and composite inorganic substance is 10-30g:50g.

6. A method for preparing a dry direct-throw recycled asphalt mixture as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: B1. Heat the composite aggregate to 180-190° C. to obtain heated aggregate; B2. Add the heated aggregate into the mixing tank, and then pre-mix the heated aggregate and the composite modifier. The pre-mixing time is 5 seconds; B3. Then add recycled asphalt into the mixing tank and mix evenly. Set the dry mixing time to 10s and the wet mixing time to 45s to obtain a dry direct-throw recycled asphalt mixture.

Citation Information

Patent Citations

  • Direct vat set modified ultra-thin wearing course asphalt mixture and construction process thereof

    CN116375394A

  • Epoxy asphalt concrete for roads and bridges and preparation method of concrete

    CN107285667A

  • Anti-rutting asphalt mixture and preparation method therefor

    CN108658509A